Juridical Analysis Of The Drafting and Formulation Of Regulations Villages in Realizing Management Principles Of Regional Empowerment and Area Development (Research Study In Bintan District) - Nina Firda Amalia; Fadlan Fadlan; Darwis Anatami; Erniyanti Erniyanti; Soeryo Respationo (FKIP, Universitas Palangka Raya, 2023)
The preparation and formulation of Village Regulations in Realizing the Management Principles of Regional Empowerment and Regional Development must go through the stages of the process of drafting and formulating draft village regulations with the aim of ensuring that the village regulations do not conflict with the public interest and/or higher statutory regulations. However, the Village Government in Bintan Regency has not implemented the stages of the process of drafting and formulating village regulations which have not been maximized, resulting in village regulations that are not in accordance with the systematicity of statutory regulations and it is feared that village regulations will conflict with the public interest and/or statutory regulations. higher invitation. The problems in this research are: How are the Legal Arrangements in the Preparation and Formulation of Village Regulations in Realizing the Principles of Management of Regional Empowerment and Regional Development, How are the Implementation of the Drafting and Formulation of Village Regulations in Realizing the Principles of Management of Regional Empowerment and Regional Development, what factors are obstacles/constraints and solutions in the Preparation and Formulation of Village Regulations in Realizing the Management Principles of Regional Empowerment and Regional Development. Based on these problems, this research uses normative and empirical legal research methods. The research results show that this arrangement does not contain definite elements of an evaluation and clarification team, and has not been running optimally in practice, there are obstacles in the field. The implementation of the stages of drafting and formulating Village Regulations has not been carried out and well coordinated so that the results of village regulations have not been optimal. The obstacles faced are the lack of knowledge, understanding and experience of village officials' human resources regarding the preparation of village regulations, the geographical location between villages and sub-districts and districts, not all of which can be reached by land and not all of them require quite a short time, coordination is not optimal. As for suggestions from the research results on the need for statutory regulations that contain an attachment to the technical format for drafting village regulations, the Regional Government of Bintan Regency can carry out outreach to all village governments regarding the preparation and formulation of village regulations, and strengthen human resource capacity.